Drinking From the Holy Grail: Analysis of Whole‐Genome Sequencing From the Genetic Analysis Workshop 18. Issue 1 (September 2014) - Paterson, Andrew D.; Paterson, Andrew; Bickeböller, Heike; Almasy, Laura
ABSTRACT The Genetic Analysis Workshops distribute real and simulated human genetic data to allow the development and comparison of methods to detect genetic variants and genes related to biological traits; the results are then presented and discussed at a biennial meeting. The data made available for Genetic Analysis Workshop 18 (GAW18) included whole‐genome sequence data for odd‐numbered autosomes from 20 large Mexican American pedigrees selected through probands with type 2 diabetes. Real and simulated blood pressure phenotype data were provided to allow the comparison of methods to detect variants and genes associated with blood pressure. Some of the complexity present in the data includes related individuals, repeated quantitative trait outcomes, covariates, medication effects, pharmacokinetic effects, missing data, admixed population, and imputed genotypes. A wide range of analytic approaches were applied to the data. Contributions that focused only on a subset of up to 155 unrelated subjects from the pedigrees were faced with low power. One recommendation for future analysis is the use of the provided null phenotype to allow comparison of type I error across methods. Collaboration between statistical geneticists and molecular biologists or bioinformaticians would provide helpful input to place variants in genes for gene‐based association tests.